Enhancing Morale through Effective Communication: A Study of Head Teacher-Teacher Interaction in Government Schools of Rawalpindi City - Saddique, Fatima; Raja, Bushra Inayat (Pakistan Languages and Humanities Review, 2022)
This qualitative study explores the critical role of effective communication in enhancing morale within Rawalpindi Government Schools, focusing on the interaction between head teachers and teachers. Twenty participants were selected using a convenience sampling technique, and face-to-face interviews were conducted to collect data. Thematic analysis was employed to analyze the obtained data, leading to the identification the main themes: The varied themes investigated in the context of effective communication within educational settings highlight the crucial significance of communication in influencing morale, engagement, operational efficiency, empowerment, and leadership dynamics. A unifying element among these themes is the acknowledgment of communication as a potent instrument capable of profoundly influencing the overall quality of educational environments. The findings of this study have significant implications for educational policy makers and all stakeholders involved in the School education system. By highlighting the importance of effective communication between head teachers and teachers, this research highlights the potential to enhance morale, leading to improved educational outcomes and overall school performance. The study's insights provide valuable guidance for the development of communication strategies and policies that can foster a positive and empowering educational environment.